Pengaruh Perubahan Kebijakan Hukum Perseroan Terhadap Isu Keberlanjutan Bisnis - Pripta Putri Pertiwi; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to analyze the impact of changes in company legal policies on business sustainability issues in the current business environment. The focus of the research is on legal policy aspects related to the company, by identifying the impact of these changes on sustainable business practices. Through document analysis and case studies, this research explores the implementation and impact of new legal policies on business sustainability practices. It is hoped that the research results will provide insight into how legal regulations influence company strategies in managing sustainability issues, including corporate social responsibility and environmental practices. The practical implications can help companies adapt strategies to regulatory changes, strengthening commitment to sustainable business practices amidst the dynamics of an ever-evolving business environment. In conclusion, changes in corporate legal policies can have a significant impact on business sustainability issues, and this research makes an important contribution to the understanding and adjustment of business practices in an era of regulatory change.